Gifts and influence: Conflict of interest policies and prescribing of psychotropic medications in the United States - King, Marissa (Soc Sci Med, 2016)
The pharmaceutical industry spends roughly 15 billion dollars annually on detailing – providing gifts, information, samples, trips, honoraria and other inducements – to physicians in order to encourage them to prescribe their drugs. In response, several states in the United States adopted policies that restrict detailing. Some states banned gifts from pharmaceutical companies to doctors, other states simply required physicians to disclose the gifts they receive, while most states allowed unrestricted detailing. We exploit this geographic variation to examine the relationship between gift regulation and the diffusion of four newly marketed medications. Using a dataset that captures 189 million psychotropic prescriptions written between 2005 and 2009, we find that uptake of new costly medications was significantly lower in states with marketing regulation than in areas that allowed unrestricted pharmaceutical marketing. In states with gift bans, we observed reductions in market shares ranging from 39% to 83%. Policies banning or restricting gifts were associated with the largest reductions in uptake. Disclosure policies were associated with a significantly smaller reduction in prescribing than gift bans and gift restrictions. In states that ban gift-giving, peer influence substituted for pharmaceutical detailing when a relatively beneficial drug came to market and provided a less biased channel for physicians to learn about new medications. Our work suggests that policies banning or limiting gifts from pharmaceutical representatives to doctors are likely to be more effective than disclosure policies alone.